Analisis Hasil Belajar Passing Bawah Dalam Permainan Bolavoli Pada Siswa SMP Negeri 1 Pinrang Kelas VIII - sutriawan, agus agus (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
This study aims to determine the learning outcomes of underpassing in volleyball games for students of SMP Negeri 1 Pinrang class VIII. This type of research is a type of descriptive research. The population in this study were all male students of class VIII SMP Negeri 1 Pinrang with a total population of 75 students with the sample used was 26 students with a sampling technique using random sampling or a random system of 35%. The research instrument used is descriptive analysis, normality analysis, and categorization with 95% truth level with the help of SPSS version 20.00 application. The results showed that: The learning outcomes of passing down in volleyball games for students of SMP Negeri 1 Pinrang in class VIII were in the Medium category or 34.6%.